This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: white (taw933) HW15 benzvi (55600) 1 This printout should have 19 questions. Multiplechoice questions may continue on the next column or page find all choices before answering. 001 10.0 points Determine the derivative of f ( x ) = 2 sin 1 ( x/ 4) . 1. f ( x ) = 4 1 x 2 2. f ( x ) = 2 1 x 2 3. f ( x ) = 2 16 x 2 correct 4. f ( x ) = 4 16 x 2 5. f ( x ) = 8 16 x 2 6. f ( x ) = 8 1 x 2 Explanation: Use of d dx sin 1 ( x ) = 1 1 x 2 , together with the Chain Rule shows that f ( x ) = 2 radicalbig 1 ( x/ 4) 2 parenleftBig 1 4 parenrightBig . Consequently, f ( x ) = 2 16 x 2 . 002 10.0 points Find the derivative of f ( x ) = parenleftBig tan 1 (2 x ) parenrightBig 2 . 1. f ( x ) = 2 4 + x 2 tan 1 (2 x ) 2. f ( x ) = sec 2 (2 x ) tan(2 x ) 3. f ( x ) = 2 1 + 4 x 2 tan 1 (2 x ) 4. f ( x ) = 4 4 + x 2 tan 1 (2 x ) 5. f ( x ) = 4 sec 2 (2 x ) tan(2 x ) 6. f ( x ) = 4 1 + 4 x 2 tan 1 (2 x ) correct Explanation: Since d dx tan 1 x = 1 1 + x 2 , the Chain Rule gives d dx tan 1 (2 x ) = 2 1 + 4 x 2 . Using the Chain Rule yet again, therefore, we see that f ( x ) = 4 1 + 4 x 2 tan 1 (2 x ) . keywords: derivative, inverse tan, Chain Rule, 003 10.0 points Determine f ( x ) when f ( x ) = tan 1 parenleftBig x 3 x 2 parenrightBig . ( Hint : first simplify f .) 1. f ( x ) = 3 3 x 2 2. f ( x ) = 1 3 x 2 correct 3. f ( x ) = x x 2 3 white (taw933) HW15 benzvi (55600) 2 4. f ( x ) = x x 2 + 3 5. f ( x ) = 3 3 + x 2 Explanation: If tan = x 3 x 2 , then by Pythagoras theorem applied to the right triangle radicalbig 3 x 2 x 3 we see that sin = x 3 . Thus f ( x ) = sin 1 parenleftBig x 3 parenrightBig . Consequently, f ( x ) = 1 3 x 2 . Alternatively, we can differentiate f using the Chain Rule and the fact that d dx tan 1 x = 1 1 + x 2 . . 004 10.0 points Find the derivative of f when f ( x ) = 5 tan 1 x 2 ln radicalbigg 1 + x 1 x . 1. f ( x ) = 7 + 3 x 2 1 x 4 2. f ( x ) = 3 7 x 2 1 x 4 correct 3. f ( x ) = 3 7 x 2 1 x 2 4. f ( x ) = 7 3 x 2 1 x 2 5. f ( x ) = 3 + 7 x 2 1 x 4 6. f ( x ) = 7 3 x 2 1 x 4 Explanation: Since ln radicalbigg 1 + x 1 x = 1 2 [ln(1 + x ) ln(1 x )] , we see that d dx bracketleftBigg ln radicalbigg 1 + x 1 x bracketrightBigg = 1 2 bracketleftbigg 1 1 + x + 1 1 x bracketrightbigg = 1 1 x 2 . On the other hand, d dx bracketleftbig tan 1 x bracketrightbig = 1 1 + x 2 . Thus f ( x ) = 5 1 + x 2 2 1 x 2 = 5(1 x 2 ) 2(1 + x 2 ) (1 + x 2 )(1 x 2 ) ....
View
Full
Document
 Spring '08
 schultz
 Differential Calculus

Click to edit the document details